2019
DOI: 10.4315/0362-028x.jfp-18-574
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Analysis for Listeria monocytogenes Growth in Ready-to-Eat Braised Beef at Dynamic and Static Conditions

Abstract: This study aimed to estimate the growth parameters of Listeria monocytogenes growth in ready-to-eat (RTE) braised beef by one-step dynamic and static kinetic analysis. The Baranyi model and cardinal parameters model were integrated into a dynamic and static model to estimate the kinetic parameters under one dynamic condition (−20 to 40.0°C) and eight static conditions (4, 8, 15, 20, 30, 35, 37, and 40°C). Based on the dynamic and static methods, the respective dynamic and static results for estimated growth bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…To illustrate his new growth model, Huang [ 25 ] applied a primary model to the growth of L. monocytogenes in broth and frankfurters but did not employ omnibus modeling. Liu et al [ 26 ] used omnibus modeling to describe the growth of L. monocytogenes in ready-to-eat braised beef. Other studies have also reported on the omnibus modeling approach [ 12 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate his new growth model, Huang [ 25 ] applied a primary model to the growth of L. monocytogenes in broth and frankfurters but did not employ omnibus modeling. Liu et al [ 26 ] used omnibus modeling to describe the growth of L. monocytogenes in ready-to-eat braised beef. Other studies have also reported on the omnibus modeling approach [ 12 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic curves combined with two static curves were used for fitting analysis to estimate the model parameters. The dynamic temperature profile was designed by referring to a previously reported study (Huang & Hwang, 2017;Liu et al, 2019) to allow for arbitrary fluctuations and incubate samples near the minimum growth temperature (T min ), thus observing the death and survival conditions of bacteria in culturing.…”
Section: Sample Incubation and Enumerationmentioning
confidence: 99%
“…The eqn (3) can be, respectively, constructed with eqn (1) and eqn (2) to obtained the inactivation kinetic parameters. The integrated ordinary differential equation (ODE) was numerically solved by the Runge-Kutta 4th numerical method as following (Jewell, 2012;Hwang & Huang, 2018;Liu et al, 2019).…”
Section: Model Construction and Validationmentioning
confidence: 99%
“…The onestep analysis based on the dynamic heating profiles may improve the accuracy of parameter estimation and simplify the test operation. These advantages have been partly validated in growth modelling in our previous study (Liu et al, 2019). To accurately understand the temperature variation of foods during the thermal process, Huang (2007) and Li et al (2018) designed a general model, which, respectively, integrated the 1-dimensional and 2-dimensional unsteady heat transfer model with the bacterial linear inactivation model to successfully simulate the dynamic inactivation of L. monocytogenes in packaged frankfurters and canned salmon roe.…”
Section: Introductionmentioning
confidence: 99%